2014
DOI: 10.1111/cdev.12292
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Relations Between Vocabulary Knowledge and Reading Comprehension: A Latent Change Score Modeling Study

Abstract: The present study followed a sample of first grade students (N = 316, mean age = 7.05 at first test) through fourth grade to evaluate dynamic developmental relations between vocabulary knowledge and reading comprehension. Using latent change score modeling, competing models were fit to the repeated measurements of vocabulary knowledge and reading comprehension to test for the presence of leading and lagging influences. Univariate models indicated growth in vocabulary knowledge and reading comprehension was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
158
4
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(195 citation statements)
references
References 57 publications
15
158
4
18
Order By: Relevance
“…To illustrate, as morphology serves as a binder of orthographic, phonological, grammatical, as well as semantic information (Bowers et al, 2010), morphological awareness facilitates more rapid and accurate decoding of morphologically complex words, and promotes an analytical approach to word learning or "morphological problem solving" (Anglin 1993: 5), and subsequently, facilitates the development of vocabulary breadth, as previous research and the present study showed (e.g., The pivotal, mediating role of vocabulary knowledge in establishing the above longitudinal relationship does not seem a surprise, given that morphology is essentially about meaning, and morphological analysis is a highly useful and reliable mechanism for acquiring meanings of new words or vocabulary growth, which is essential to textual comprehension (Authors 2012b;Perfetti, 2007;Quinn et al 2015). Such a finding also corroborates that of Goodwin et al (2013) Given the critical import of morphology in reading comprehension, it seems puzzling that a unique, longitudinal effect of morphological awareness failed to emerge in the current study.…”
Section: Direct and Indirect Effects Of Morphological Awareness On Resupporting
confidence: 74%
“…To illustrate, as morphology serves as a binder of orthographic, phonological, grammatical, as well as semantic information (Bowers et al, 2010), morphological awareness facilitates more rapid and accurate decoding of morphologically complex words, and promotes an analytical approach to word learning or "morphological problem solving" (Anglin 1993: 5), and subsequently, facilitates the development of vocabulary breadth, as previous research and the present study showed (e.g., The pivotal, mediating role of vocabulary knowledge in establishing the above longitudinal relationship does not seem a surprise, given that morphology is essentially about meaning, and morphological analysis is a highly useful and reliable mechanism for acquiring meanings of new words or vocabulary growth, which is essential to textual comprehension (Authors 2012b;Perfetti, 2007;Quinn et al 2015). Such a finding also corroborates that of Goodwin et al (2013) Given the critical import of morphology in reading comprehension, it seems puzzling that a unique, longitudinal effect of morphological awareness failed to emerge in the current study.…”
Section: Direct and Indirect Effects Of Morphological Awareness On Resupporting
confidence: 74%
“…The strength of these mutual relations between abilities are captured in the M matrix in the mutualism model and can be both unidirectionalas for example in investment theory where growth in crystallized intelligence is fueled by niet growth in, maar juist 'level' fluid intelligence Cattell (1971) -or bidirectional. These bidirectional facilitating relations have previously been observed between the development of cognitive strategies and short-term memory (Siegler and Alibali, 2005), vocabulary and reading ability (Quinn et al, 2015) and between subjective and objective memory in aging (Snitz et al, 2015). In mathematics, van der Ven et al (2012) found a positive interactions between changes in math skills and changes in working memory, suggesting mutual influences in their development.…”
Section: Two Different Theories Of Cognitive Developmentsupporting
confidence: 59%
“…The no-coupling model resembles the correlated growth model of Quinn et al (2015) and functions as a baseline model which we test against to determine the presence of significant coupling parameters. Also, as indicated by a simulation study (see Appendix B), if the coupling parameters are set to zero the model fit of the no-coupling model resembles the model fit of the g-factor model, which further supports its use as a baseline model.…”
Section: Modeling Framework: Latent Change Score Modelsmentioning
confidence: 99%
“…Quinn, Wagner, Petscher & Lopez [14] stated that words are organized into an intricate, interlocking system, therefore they cannot be learned in isolation without considering their related context. McKeown & Curtis [15] have found strong correlations between vocabulary knowledge and reading comprehension.…”
Section: Vocabulary Pre Teachingmentioning
confidence: 99%